STUDI PERBANDINGAN PERKEMBANGAN KECAMATAN PAUH DAN KECAMATAN MANDIANGIN DI KABUPATEN SAROLANGUN - Ahmad Efendi; Sri Mariya (DEPARTEMEN GEOGRAFI FIS UNP, 2019)
The study to porpuse determine the development of Pauh and Mandiangin Subdistricts in terms of economy, facilities and the influence of location factors in the comparison of the development of Pauh and Mandiangin Districts. This type of research is quantitative descriptive using area sampling techniques. Based on the results of the study found (1) Each sub-district has its own base sector. The economic comparison between Pauh and Mandiangin Districts is dominated by Mandingian District. (2) The development of facilities in Mandiangin District is better than Pauh Subdistrict and road infrastructure in Mandiangin District faster than Pauh Subdistrict, it has even reached 90% of asphalt roads in 2017. (3) Mandiangin District has more interaction to Muara Bulian and Jambi City which is a larger city center in Jambi Regency. So that with this trend, the development in this Subdistrict is better than the parent sub-district, namely Pauh District.